Respiratory symptoms among search and rescue workers who responded to the 2016 Taiwan earthquake. Issue 9 (10th July 2018) - Wu, Chen-Long; Lan, Fan-Yun; Chen, Bo-Lei; Chang, Ray Hsienho; Chang, Wei Hung; Pan, Shih-Tien; Fang, Pin-Hui; Lu, Chien-Hsin; Lin, Chih-Hao
Abstract : Objectives: High respiratory hazards among search and rescue workers (SRWs) emerged after the World Trade Center attacks on 11 September 2001. There have been limited studies on respiratory symptoms among earthquake SRWs. We investigated the respiratory symptoms and the use of respiratory protective equipment among the SRWs who responded to the 2016 Taiwan earthquake. Methods: On 6 February 2016, a 6.4-magnitude earthquake struck southern Taiwan and caused 513 injuries and 117 deaths. During the 9-day field operation, 519 firefighters affiliated with the Tainan City Government Fire Bureau participated in the search and rescue response. A standardised, self-completed questionnaire was used to collect data on demographics, dust exposures, personal protective measures and health outcomes 3 weeks after the earthquake. Descriptive and multivariate analyses adjusting for demographics and exposure variables were performed for new or worsened outcomes. Results: Of the 519 SRWs, 414 (80%) responded to the questionnaire. Of these SRWs, 153 (37%) reported new or worsened respiratory symptoms, with cough (23%) as the leading symptom, followed by rhinorrhoea or nasal congestion (22%) and chest tightness (6%). More than 90% of the symptoms persisted to the third week after the earthquake. The prevalence of new or worsened respiratory symptoms was significantly higher among SRWs with a higher level of exposure to dust. Prior training in response to respiratory pollutants was only 5%. Conclusions: There were significant respiratory hazards among earthquake SRWs. The persistent symptoms and low coverage of training warrant further regular examination and occupational health programmes.